1987
DOI: 10.1021/ie00070a034
|View full text |Cite
|
Sign up to set email alerts
|

Coke formation on polished and unpolished Incoloy 800 coupons during pyrolysis of light hydrocarbons

Abstract: The objective of this study was to determine if polishing Incoloy 800 metal coupons significantly reduced coke formation during pyrolysis of light hydrocarbon feedstocks. All experiments were conducted at 700 °C, 1 atm, and 1-h contact and using methane, ethane, ethene, propane, propene, and isobutane. The ratio of carbon formed from the unpolished coupons to that from polished varied from a low of 5.6 for isobutane up to 28.1 for ethene; most were between 5.6 and 7.9. The polishing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
5
16
0
Order By: Relevance
“…The results in Table S.2 indicate that when changing the initial surface roughness of 0.15 to 2.6 μm, the amount of coke deposited in the first cracking cycle remains rather stable while for the initial surface roughnesses of 3.9–7.0 μm, the amount of coke is 20–30% higher. Qualitatively, these observations are in line with earlier work by Marek and Albright , and Crynes and Crynes . Although the pretreatment and operating conditions in these studies were strongly different from those in the current study, these authors also observed that polishing reduced coke deposition on Incoloy 800 , and aluminized Incoloy 800 coupons in the pyrolysis of light hydrocarbons.…”
Section: Results and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results in Table S.2 indicate that when changing the initial surface roughness of 0.15 to 2.6 μm, the amount of coke deposited in the first cracking cycle remains rather stable while for the initial surface roughnesses of 3.9–7.0 μm, the amount of coke is 20–30% higher. Qualitatively, these observations are in line with earlier work by Marek and Albright , and Crynes and Crynes . Although the pretreatment and operating conditions in these studies were strongly different from those in the current study, these authors also observed that polishing reduced coke deposition on Incoloy 800 , and aluminized Incoloy 800 coupons in the pyrolysis of light hydrocarbons.…”
Section: Results and Discussionsupporting
confidence: 93%
“…Qualitatively, these observations are in line with earlier work by Marek and Albright , and Crynes and Crynes . Although the pretreatment and operating conditions in these studies were strongly different from those in the current study, these authors also observed that polishing reduced coke deposition on Incoloy 800 , and aluminized Incoloy 800 coupons in the pyrolysis of light hydrocarbons. As stated previously, these authors did not measure the difference of roughness induced by polishing.…”
Section: Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regard to the chemical composition, many studies have shown that some metals, such as Fe, Ni, and Mo, on the surface of the reaction channels have a catalytic effect for coking, while other metals, such as Cu, Si, Al, Cr, Ti, Nb, and Ta, are found to inhibit coking [18][19][20]. With regard to the surface roughness, Crynes et al [21] examined the effect of surface roughness on coke formation during the pyrolysis of light hydrocarbon feedstock using polished metal coupons of Incoloy 800. The results showed that the coking rate reduced sharply after polishing; the ratio of carbon formed on the unpolished coupons to the polished ones varied from 5.6 for iso-butane to 28.1 for ethene.…”
Section: Introductionmentioning
confidence: 99%